Desempenho zootécnico e caracterização do crescimento muscular do pintado amazônico (fêmea Pseudoplathystoma reticulatum x macho Leiarius marmoratus), após restrição alimentar - Cotrim, Thiago Santana (2015)
Among the fish grown on a large scale in Brazil, one can cite the Pintado Amazônico (Pseudoplathystoma reticulatum X Leiarius marmoratus), that has high market value. The compensatory growth is characterized by elevated weight gain after a limited period of development, usually because of reduced feed intake. The study was conducted at company Delicious Fish in the Sorriso-MT city. The objective of this study was to evaluate the compensatory growth of the hybrid Pintado Amazônico, at different levels of feed restriction. Were used four hundred animals, with initial weight of 15g that were randomly distributed into four tanks, with density of 100 fish / and acclimated, for 15 days and a trial period of 120 days. The animals were divided into four groups with different restriction levels based on the percentage of body weight (G1 = 5%, G2 = 2%, G3 and G4 = 0.5% = 0%. The restriction period was 30 days following a period of refeeding for 90 days. After the restriction period, all fish were fed 5% weight twice a day. After the trial period, 10 animals per group were collected. We carried out the evaluation of the production performance such as weight gain, condition factor, feed conversion and visceral fat index. For of growth performance data was used linear mixed model , the averages compared by Krammer Tukey test , adopting a significance level of 5 % significance. The muscle tissue samples were processed using PAS staining with metanil yellow. Subsequently was accomplished the cellular morphology, through which measured the areas of each muscle cell in cross section in the approximate number of 2500 cells for each group. Data were divided into classes according to the cell area , and subjected to statistical analysis according Krammer Tukey test at 5 % significance. The results indicate that the pintado amazônico in the juvenile stage, according to the weight gain, presented a total compensatory growth when submitted to partial food restriction of 2% and 0.5% of body weight, however, the total feed restriction diet with 0% of body weight was a negative factor for the total compensatory growth. The total compensatory growth through hypertrophic growth of muscle cells, occurred 15 days from return feed in G2, 60 days return feed on G3 and with 90 days of return feed on G4, whitch showed a partial compensatory growth. A reduction in the diet at 2% and 0.5% of body weight over a period of fasting did not affect the hyperplastic growth of muscle cells during refeeding, although stimulated an xiii ascendant hyperplasia of muscle cells G4 from the period 60 days. A partial restriction strategy up to 0.5 % of body weight at 90 days of refeeding did not interfere efficient feed conversion (p> 0.05). A partial restriction strategy to a limit of 0.5% of body weight did not result in decreases in condition factor (p > 0, 05). The partial restriction strategies of 2% and 0.5% showed greater accumulation of visceral fat (p < 0, 05). It concluded that the compensatory growth strategy for the Amazonian catfish in the juvenile stage was most efficient within a 30-day restriction period and a feed restriction 0.5% of body weight can be used in the production systems for benefit these production.